Waveguiding and Lasing in 2D Organic Semiconductor Znq2. Issue 2 (28th December 2020) - Lin, Shenghuang; Li, Tenghao; Yuan, Jian; Liao, Liangsheng; Tao, Jin; Kan, Ruifeng; Xu, Xuhui; Bao, Qiaoliang
Abstract : Organic semiconductors have been proven as emerging platforms for exploring strong light–matter interactions and quantum optics so as to develop coherent and quantum photonic devices. Though there has been abundant research on organic semiconductors, lasing action is rarely reported in individual 2D organic semiconductor waveguides or nanocavities. Herein, a strong optical waveguiding phenomenon is observed not only in the individual 2D organic semiconductor Znq2 nanosheet with micrometer size area, but also in the interconnecting or neighboring Znq2 nanosheets. The optical propagation loss coefficient of the interconnecting Znq2 sheets is ≈800 dB cm −1 . More importantly, the phenomenon of optically pumped lasing in 2D Znq2 nanosheets is demonstrated, as evidenced by a sudden increase in emission intensity at a threshold pump pulse fluence of 49.9 W cm −2 at 480 nm. As verified by numerical FDTD simulations, the Znq2 nanosheet constitutes a microcavity that supports whisper gallery mode, providing suffcient feedback for laser oscillations. Herein, the coexistence of low‐loss waveguiding and excellent lasing in 2D organic semiconductor nanosheets are revealed, which open up a new pathway for photonics and quantum optics based on 2D organic semiconductors. Abstract : Herein, a strong optical waveguiding property is found not only in the individual 2D organic semiconductor Znq2 nanosheet, but also shown in the arrays of Znq2 nanosheets. Optically pumped lasing action in the studied Znq2 nanosheets is also demonstrated, which opens up a new pathway for photonics and quantum optics based on 2D organic semiconductors.